Nasal vaccination against Trypanosoma cruzi: a dual approach for prevention and treatment of chronic Chagas cardiomyopathy - Cacik, Paula; Pacini, Maria Florencia; Bulfoni Balbi, Camila; Dinatale, Brenda; Diaz, Genaro; Cha, Ulises; Farré, Cecilia; Gianeselli, Mónica; Prochetto, Estefanía; Peréz, Ana Rosa; Marcipar, Iván Sergio (Frontiers in Immunology, 2025)
Chagas disease, caused by the parasite Trypanosoma cruzi (T. cruzi), is a neglected life-threatening disease. Given that available pharmacologic treatments are effective only in the acute phase, and that diagnosis typically occurs during the chronic phase when cardiac damage is already present, current efforts should aim to mitigate cardiac pathology during chronic infection. This study evaluates the effectiveness of a nasal vaccine based on trans-sialidase (TS) plus c-di-AMP in both prophylactic and therapeutic settings against chronic Chagas cardiomyopathy (CCC) in a mouse model of T. cruzi oral infection. Prophylactic and therapeutic vaccination significantly reduced cardiac inflammation, fibrosis, and parasite load. Histological analysis confirmed less cardiac damage in vaccinated groups compared to infected, unvaccinated controls. While electrocardiographic abnormalities were fully prevented in the prophylactic group, therapeutic vaccination still halved arrhythmia incidence, indicating functional benefits despite late administration. Immunologically, both vaccine regimens promoted a Th17-skewed response, with increased IL-17 expression in cardiac tissue. However, distinct immune signatures were observed: prophylactic vaccination reduced TGF-β and T-bet expression, correlating with less fibrosis and inflammation; therapeutic vaccination elevated Foxp3, suggesting regulatory T cell involvement in controlling chronic inflammation. Both strategies enhanced TS-specific antibodies and reduced non-protective, parasite-wide antibody responses, shifting the humoral profile toward functional protection. Importantly, vaccinated animals also showed a marked reduction in heart auto-reactive antibodies. The findings suggest that early intervention yields greater benefits, but even post-infection, immunization can also significantly mitigate cardiac damage. These results underscore the potential of nasal TS-based vaccines as a non-invasive, dual-action strategy to both prevent and treat CCC.